Isolation and characterization of Leuconostoc oenos bacteriophages from wine and sugarcane and the occurrence of temperate bacteriophages in strains of L. oenos - Mouton, Louise (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.